Serum and salivary ferritin and Hepcidin levels in patients with chronic periodontitis and type 2 diabetes mellitus - Lin-Na Guo; Yan-Zong Yang; Yun-Zhi Feng (BMC, 2018)
Abstract Background Iron disorder and abnormal expression of hepcidin play important roles in many diseases, but it is still unclear in chronic periodontitis (CP) and type 2 diabetes mellitus (T2DM). We aimed to assess ferritin and hepcidin levels in serum and saliva of CP patients with or without T2DM. Methods Serum and unstimulated whole saliva samples were collected from 88 participants, who were categorized into 4 groups based on the presence or absence of CP or T2DM. Demographics and general health parameters were recorded. Full-mouth clinical periodontal parameters including probing pocket depth, clinical attachment loss, bleeding index, and plaque index were recorded. Chemiluminescence microparticle immunoassay and enzyme-linked immunosorbent assay were used to detect ferritin and hepcidin concentrations, respectively, in serum and saliva. Results Serum ferritin and hepcidin levels in the CP and CP with T2DM groups were higher than in the control group (P < 0.05). Serum hepcidin and serum ferritin are linear correlated (P < 0.001). Serum hepcidin/ferritin values in the CP with T2DM group were significantly lower than those in the T2DM and control groups. Moreover, salivary ferritin levels in the CP and T2DM groups were higher than those in the control group (P < 0.05). There was positively correlation between salivary ferritin and serum ferritin (P = 0.017). Hepcidin concentrations were relatively low in saliva. Conclusions These results suggest that iron overload and hepcidin inadequacy existed in CP with T2DM patients. Salivary ferritin might provide a reference for body iron load. Trial registration ChiCTR-ROC-17012780